Lost or misplaced settlements: the cases of the medieval settlements of Cleeton and Nuttle in Holderness, East Yorkshire - Newman, Richard (Medieval Settlement Research, 2024)
Describing a medieval settlement as ‘lost’ was a frequent way of defining deserted medieval settlements in the early and mid-twentieth century. At the time, a settlement often could be noted as having existed in the historical record but was no longer recognised as extant and often was not identifiable as an archaeological site. The term ‘lost’ was applied to settlements that were longer extant (including those that might be identifiable as archaeological remains) and to those that had been destroyed by natural processes, especially coastal erosion. Rather than lost, however, some may have been misplaced through misunderstanding. This paper presents evidence that such misplacement has occurred in the cases of Cleeton and Nuttle in the East Riding of Yorkshire.